Closing Windows During Covid-19: How New Brunswick Media Framed a Pandemic - Steuter, Erin; Martin, Geoff (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2023)
The New Brunswick English-language news media’s coverage of the COVID-19 pandemic from March 2020 through May 2021 is examined utilizing a frame analysis. The media provided significant essential information but frequently did not address social, political, and economic factors that exacerbated the health crisis. New Brunswick’s experience of the pandemic was conditioned by structural factors, which opened a policy window for a transition away from neoliberal austerity to a stronger health and social safety. The news media played a role in closing these policy windows by failing to investigate and elucidate the policy causes and solutions at play during the pandemic.